Carbon Tax Policy Toward Net Zero Emission - Purwienanti Eiffeliena N.F.; Purwanto Purwanto (E3S Web of Conferences, 2023)
The use of fossil fuels as a primary energy source aims to meet the supply of energy needs. However, it is causing detrimental impacts on the environment in the form of pollutants and emissions of carbon dioxide as a greenhouse gas that have the potential for global warming. The net zero emission targets of various countries in 2050 and 2060 are used as a driving force to reduce the use of energy sources that cause greenhouse gas emissions. Furthermore, using renewable energies such as wind, solar, water and biomass energy replace fossil energy in an effort toward net zero emission. The policies of various countries to implement a carbon tax encourage renewable energy use to reach the net zero emission target. Indonesia targets net zero emission to be achieved by 2060 or even earlier. Thus, by 2030, it is targeted to reduce greenhouse gas emissions by 41% from BAU (business as usual) with international assistance and 26% without international assistance. Sweden's success in implementing a carbon tax starting in 1991, which has reduced greenhouse gas emissions by 35%, can be an example for other countries to implement a taxation system on fossil energy. The carbon tax implementation in Indonesia gradually starts on July 1, 2022, limited to coal-fired power plants (PLTU). It uses a cap and tax scheme, with tariffs applied to the number of emissions exceeding the set cap. Therefore, taxpayers can also take advantage of carbon certificates purchased on the carbon market to reduce their tax obligations.